Core-periphery structure of a medicinal botanical system in Uruguay - Elena Castiñeira Latorre; Ana Inés Borthagaray; Andrés Canavero (BMC, 2024)
Abstract Background Human evolution has granted upon an individual's cognitive mechanisms necessary for remembering experiences, vital for both survival and reproduction. These experiences manifest into cultural traits, influencing human culture, particularly in healthcare and maintenance. Studies regarding medicinal plants and treatments are integral to the study of the medical botanical system. Pharmacopeias highlight the prevalence of specific species widely used, aligning with the "consensus within diversity theory" in evolutionary ethnobiology. Within the framework of this theory, we reflect on the results we've achieved in a priority area recognized by UNESCO for its biocultural significance, both locally and regionally. Methods This study integrated network analysis and qualitative methods to examine the botanical medical system of "Parque Regional Quebradas del Norte" in Rivera, Uruguay. Results Study results demonstrate a core-periphery structure, with a strongly interconnected core resistant to fragmentation, ensuring structural stability. Additionally, the presence of peripheral nodes throughout the system was identified, enhancing the resilience of the botanical medicinal system against potential disturbances. Conclusion The core species renowned for their versatility and multiple medicinal uses, treating less severe ailments effectively. Additionally, core plants serve as prototypes for innovations. Their extinction poses a threat to the system's resilience. Conversely, peripheral plants, though vulnerable, offer possibilities for therapeutic innovations. In the face of environmental change, conservation efforts should prioritize species that are vulnerable to extinction, particularly within the core. Simultaneously, preserving knowledge associated with peripheral plants presents a bicultural conservation strategy, ensuring the botanical system's robustness among evolving ecological conditions.